Lysosomal biogenesis and function in osteoclasts: a comprehensive review - Jiang, Junchen; Ren, Rufeng; Fang, Weiyuan; Miao, Jiansen; Wen, Zijun; Wang, Xiangyang; Xu, Jiake; Jin, Haiming (Frontiers in Cell and Developmental Biology, 2024)
Lysosomes serve as catabolic centers and signaling hubs in cells, regulating a multitude of cellular processes such as intracellular environment homeostasis, macromolecule degradation, intracellular vesicle trafficking and autophagy. Alterations in lysosomal level and function are crucial for cellular adaptation to external stimuli, with lysosome dysfunction being implicated in the pathogenesis of numerous diseases. Osteoclasts (OCs), as multinucleated cells responsible for bone resorption and maintaining bone homeostasis, have a complex relationship with lysosomes that is not fully understood. Dysregulated function of OCs can disrupt bone homeostasis leading to the development of various bone disorders. The regulation of OC differentiation and bone resorption for the treatment of bone disease have received considerable attention in recent years, yet the role and regulation of lysosomes in OCs, as well as the potential therapeutic implications of intervening in lysosomal biologic behavior for the treatment of bone diseases, remain relatively understudied. This review aims to elucidate the mechanisms involved in lysosomal biogenesis and to discuss the functions of lysosomes in OCs, specifically in relation to differentiation, bone resorption, and autophagy. Finally, we explore the potential therapeutic implication of targeting lysosomes in the treatment of bone metabolic disorders.